Changes in body temperature of critically ill patients submitted to bed bathing: a crossover clinical trial - Luana Vieira Toledo; Bárbara Xavier dos Santos; Patrícia de Oliveira Salgado; Laylla Meireles de Souza; Lídia Miranda Brinati; Carla de Fátima Januário; Flávia Falci Ercole
ABSTRACT Objectives: to compare tympanic and axillary body temperature values of critical patients before and after the traditional and dry bed bath. Methods: this is a randomized, open crossover clinical trial conducted with 50 adult critical patients. All patients received both types of bed bathing. The tympanic and axillary temperature values were measured at the beginning and end of the baths. The Wilcoxon test or paired Student's t test was used. Results: elderly and male patients predominated. There was no significant difference between tympanic temperature medians measured during the traditional bed bath (p=0.707) and dry bath (p=0.101). Axillary temperature means reduced at the end of the baths (p=0.001), being 36.12ºC in the traditional bath and 35.92ºC in dry bath. Conclusions: bed bath, regardless of the method used, caused a reduction in critical patients' axillary temperature.